A new species of Fomitiporia (Hymenochaetales) from Australia - Chen, Jia-Jia; Wu, Ying-Da; Ji, Xiao-Hong; Gates, Genevieve; Xu, Xiang (Phytotaxa, 2021)
A new species of Fomitiporia, F. tasmanica, is described from Tasmania (Australia) based on morphological examination and phylogenetic analysis of the nuc rDNA region encompassing the internal transcribed spacers 1 and 2, along with the 5.8S rDNA and nuc 28S rDNA D1-D2 domains. The new species is characterized by perennial, resupinate basidiocarps, very small pores (10–12 per mm), a dimitic hyphal system, presence of hymenial setae and cystidioles, and subglobose basidiospores measuring 5.5–6.6 × 5–6 µm.